2017
DOI: 10.3390/met7100408
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Properties and Fracture Behavior of a Powder-Thixoformed 2024Al/SiCp Composite at Elevated Temperatures

Abstract: Abstract:In the present work, the tensile properties and fracture behavior of a 2024Al composite reinforced with 10 vol % SiC p and fabricated via powder thixoforming (PT) were studied at temperatures ranging from 25 • C to 300 • C with a strain rate of 0.05 s −1 , as well as the PT 2024 alloy. The results indicated that the tensile strengths of both the PT materials were all decreased with increasing the temperature, but the decrease rate of the composite was smaller than that of the 2024 alloy, and the compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Atrian et al pointed out that the properties of SiC particles did not change significantly during the temperature increase, while the 6061 aluminum alloy matrix softened and the dislocations mobility increased with the increasing temperature to reduce the tensile strength of composites [21]. The phenomenon was also similar to that obtained by Li et al with SiC p /2024Al composites [22]. For direct strengthening, external stress is generally transmitted from the matrix to the reinforcement through the interface.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…Atrian et al pointed out that the properties of SiC particles did not change significantly during the temperature increase, while the 6061 aluminum alloy matrix softened and the dislocations mobility increased with the increasing temperature to reduce the tensile strength of composites [21]. The phenomenon was also similar to that obtained by Li et al with SiC p /2024Al composites [22]. For direct strengthening, external stress is generally transmitted from the matrix to the reinforcement through the interface.…”
Section: Resultsmentioning
confidence: 56%
“…For direct strengthening, external stress is generally transmitted from the matrix to the reinforcement through the interface. Li et al reached this conclusion through a calculation that showed that high temperature degraded the load-transfer strengthening [22]. For indirect strengthening, dislocation strengthening is significantly dependent on the density of dislocations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation